THEORETICAL PRINCIPLES OF IMPROVING CREATIVE THINKING OF STUDENTS ON THE BASIS OF MODERN EDUCATIONAL APPROACHES - Maftuna Abdumajitova (Western European Studies, 2023)
In the article, the development of creative thinking of students based on current modern approaches, the role of the teacher in this process, knowing the age periods favorable for the development of creativity and following the necessary principles during the lesson, at the same time, allocating time to perform tasks and the importance of evaluation is considered.
Keywords: creativity; creative potential; development; thinking